Optimizing British Vocal Pedagogy Strategies Based on Learner Psychological Adjustment: An Inquiry - Wang, Yihan (Education Insights, 2026)
This study investigates the optimization of British vocal pedagogy through the systematic integration of learner psychological adjustment principles. While traditional training emphasizes technical proficiency, it often neglects learners' psychological states such as performance anxiety, motivation, and self-efficacy. To address this gap, the research employs a mixed-methods approach, conducting case studies across three distinct pedagogical contexts: conservatoire classical training, performing arts college musical theatre, and private studio contemporary commercial music coaching. The findings demonstrate that psychologically-informed teaching strategies significantly enhance key outcomes, including anxiety reduction, increased learner autonomy, and improved technical and expressive performance. However, the implementation must be context-sensitive, adapting to specific cultural and structural settings. The study concludes by proposing an integrative psycho-pedagogical framework that equips vocal instructors with adaptable tools to support holistic singer development, thereby bridging the gap between technical rigor and psychological well-being in vocal education.